Knowledge level, attitude, and behavior of midwifery students about periodontal health to pregnant women: Gambaran tingkat pengetahuan, sikap dan perilaku mahasiswi kebidanan tentang kesehatan periodontal terhadap ibu hamil - Armia Syahputra; Zulkarnain; Pitu Wulandari; Sonia Mulyani Sinaga (Makassar Dental Journal PDGI Makassar, 2022)
Periodontal disease is an inflammatory disease of the tissues surrounding the teeth. Periodontal disease during pregnancy is cor-related with adverse pregnancyoutcomes such as prematurity, low birth weight, preeclampsia, and miscarriage. Midwifery stu-dents who will practice need to know about periodontal health inpregnant women. This descriptive study is aimed to determine the knowledge, attitudes and behavior of midwifery students at STIKes Senior Medan about periodontal health for pregnant women, with the number of research samples was 102 female students. The tests used are validity tests, reliability tests and des-criptive statistical analysis. The questionnaire is valid and reliable except for items number 3 for knowledge and 5 for attitude so it is deleted. The resultsshowed that the level of knowledge and attitudes and behaviour of STIKes senior midwifery students about the periodontal health of pregnant women is in the good category.